2010
DOI: 10.1111/j.1755-3768.2010.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual function in 6 to 7 year‐old children born extremely preterm: a population‐based study

Abstract: ABSTRACT.Purpose: Progress in neonatal care has caused an increased survival of children born extremely preterm. The aims of this study were to examine the long-term visual function and ocular development in an unselected cohort of extremely preterm infants and relate the results to neonatal morbidity and long-term neurodevelopmental outcome. Methods: All children with gestational age of 22-27 completed weeks or birth weight of 500-999 g born in the years 1999-2000 in two counties of Western Norway (n = 52) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
14
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
8
14
2
Order By: Relevance
“…O’Connor et al22 reported that 20.5% of preterm eyes become more hyperopic at age 10 years. In accordance with Haugen et al23 our study showed that hypermetropic refractive error was prevalent between 0 D and 3 D rather than >3 D at both visits (Figure 2). High hyperopia was found in only one child, who was affected by microphthalmia and severe ROP, which was treated with cryotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…O’Connor et al22 reported that 20.5% of preterm eyes become more hyperopic at age 10 years. In accordance with Haugen et al23 our study showed that hypermetropic refractive error was prevalent between 0 D and 3 D rather than >3 D at both visits (Figure 2). High hyperopia was found in only one child, who was affected by microphthalmia and severe ROP, which was treated with cryotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, few children were myopic (3.1%). This was similar to a finding of no myopia in kindergarten children in Denmark (Sandfeld et al 2018) but is low compared to most ROP cohorts (Al Oum et al 2014, Fledelius et al 2015Haugen et al 2012). A high number had astigmatism compared to the studies by Fledelius (Fledelius et al 2015) (14.6%, cylinder ≥ À0.75D) and Sandfeld (Sandfeld et al 2018) (4.3%, cylinder ≥ À1.0D).…”
Section: Discussionsupporting
confidence: 82%
“…Currently, few children in Denmark become visually impaired due to ROP (Jensen 2018), presumably due to advances in treatment, screening and postnatal care, even though more extremely preterm children survive. A Danish study of children born at gestational age ≤ 28 weeks showed that cerebral damage was a more frequent cause of vision impairment than was ROP (Slidsborg et al 2012), which is in agreement with other studies of preterm children (Boonstra et al 2012;Haugen et al 2012;Siatkowski et al 2013;Holmstrom et al 2014;Leung et al 2018).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…2,24,25 Preterm infants with prolonged duration of mechanical ventilation may become dependent on the ventilator. 2 In addition, prolonged mechanical ventilation increases the risk for chronic lung disease.…”
Section: Chronic Lung Disease Subglottic Stenosis Retinopathy Of Prmentioning
confidence: 99%